Knowledge of obesity and its effects on cardiometabolic and reproductive health in women - Eti, Manorama; M.P., Chandana; B.M., Roopkala; R., Nagarathnamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Obesity is following a raising trend in India. Being a major risk factor for various diseases, awareness should be raised among people regarding this issue. The objective of the study was to assess knowledge of obesity and its ill effects on cardio metabolic and reproductive health in women. Methods: This was a prospective survey study done on women visiting gynecology OPD at Rajarajeswari Medical College and Hospital. 300 Subjects were randomly picked and were administered a questionnaire on the health risks of obesity, that is, its effect on cardio metabolic status, reproductive outcome in terms of infertility and spontaneous abortions and obesity related cancers such as endometrial and breast cancers. Height and weight measurements of the study subjects were measured. Results: Subjects’ age ranged from 19 to 47 years (mean SD: 28.72 ± 6.52). subjects who were aware that obesity increases the risk of various diseases were: diabetes (85.3% ) , blood pressure (88.7%), raised cholesterol levels in the blood(90.7%), infertility (84%), irregular periods (62%), abortions (44%),arthritis (86.7% ), breast cancer (36%) , endometrial cancer (36.7% ). Conclusions: Women in our study have good knowledge about obesity and its effect on general health and cardio metabolic diseases, fair knowledge about reproductive outcomes. They are less aware of the association of obesity and sex hormone sensitive cancers like endometrial and breast cancers. Public education is needed to increase awareness of obesity and malignancy.